Media and development: the politics of framing gender struggles in the postcolonial zimbabwean shona films - Rwafa, Urther (Taylor & Francis (Routledge), 2017)
To frame gender struggles is to set an agenda on what people should think about it in respect of the contradictory roles that men and women play in society and culture. In this article, three films in the Shona language – Mwanasikana (1995), Kapfupi (2009) and Nhasi tave nehama (1993) have been sampled out to explore gender struggles inherent in the Zimbabwean society. The premise of this article is rooted in the ideological doubleness of the word framing as both restrictive as well as an instrument for liberation. Framing gender in the discourses of these three films calls attention to perceiving gender struggles in certain ways and in the process mani-festing as far as possible the buried narratives that are otherwise obscured in mani-pulated forms of representing life. It is the duty of film critics to retrieve these silenced and “other”readings because of their potential to suggest to the audiences some alternative opinions and reactions. I advance in this article that while a framecan impose what should be thought about, it does not necessarily dictate how audiences interpret its text(s). This dialectical relation of framing implied in the restriction-liberating dimension of a frame, that emerges as it were from the struggle of verbal and visual images inside a frame’s boundaries, actually can predispose audiences to want to delve for alternative images of how men and women are depicted in the Shona film.